2020
DOI: 10.1111/cas.14399
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S6 promotes stem‐like characters in glioma cells

Abstract: Glioblastoma multiforme (GBM), a lethal brain tumor developing in the white matter of the adult brain, contains a small population of GBM stem cells (GSCs), which potentially cause chemotherapeutic resistance and tumor recurrence. However, the mechanisms underlying the pathogenesis and maintenance of GSCs remain largely unknown. A recent study reported that incorporation of ribosomes and ribosomal proteins into somatic cells promoted lineage trans‐differentiation toward multipotency. This study aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…Ribosomes are subcellular cytoplasmic biomolecules composed of rRNA and dozens of proteins that primarily participate in translation [ 40 , 41 ]. Recent studies have shown that ribosomes are involved in multiple biological processes, such as cellular proliferation, differentiation, homeostasis, and development of cancer [ 40 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosomes are subcellular cytoplasmic biomolecules composed of rRNA and dozens of proteins that primarily participate in translation [ 40 , 41 ]. Recent studies have shown that ribosomes are involved in multiple biological processes, such as cellular proliferation, differentiation, homeostasis, and development of cancer [ 40 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated CSCs are known to maintain low levels of global translation and degradation activity, but they need to respond to dynamic alterations in the tumor environment during disease progression by rapidly regulating protein translational programs [ 44 46 ]. Maintaining the ability of CSCs to undergo self-renewal requires high translation efficiency [ 41 , 45 , 47 ], and inhibiting translation in CSCs has the potential to reduce their stem-like properties [ 48 ]. Our data revealed that EVs released by NSCCs contain cargos enriched in ribosomal proteins that could be taken up and utilized by CSCs to rapidly induce protein synthesis, enabling these cells to adapt to a dynamic tumor environment.…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated CSCs are known to maintain low levels of global translation and degradation activity, but they need to respond to dynamic alterations in the tumor environment during disease progression by rapidly regulating protein translational programs (44)(45)(46). Maintaining the ability of CSCs to undergo self-renewal requires high translation e ciency (41,45,47), and inhibiting translation in CSCs has the potential to reduce their stem-like properties (48). Our data revealed that EVs released by NSCCs contain cargos enriched in ribosomal proteins that could be taken up and utilized by CSCs to rapidly induce protein synthesis, enabling these cells to adapt to a dynamic tumor environment.…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al reported that ribosome incorporation into somatic cells depends on trypsin-activated endocytosis and ribosomes may interact with several intrinsic cell signals. Meanwhile, our recent studies revealed that ribosomal proteins are overexpressed at border niches in GBM tissues [ 15 ]. A recent study also showed that translation of ribosomal RNA and nucleolar regulation promoted glioma tumorigenesis, such as stem cell characters [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that translation of ribosomal RNA and nucleolar regulation promoted glioma tumorigenesis, such as stem cell characters [ 16 ]. Furthermore, we also revealed that ribosome including RPS6 played crucial roles in stem-like characters in glioma cells in GBM patients [ 15 ]. However, the relationship between GSC development and ribosome incorporation as a key trigger for reprogramming is totally unknown.…”
Section: Introductionmentioning
confidence: 99%